245 Clinical and immunogenetical characteristic of celiac disease in paediatric patients from single tertiary centre. (11th October 2021) - Ivančić, Jana; Žunec, Renata; Grubić, Zorana; Aničić, Mirna; Omerza, Lana; Tješić-Drinković, Duška; Vuković, Jurica; Senečić-Čala, Irena
Abstract : Celiac disease (CD) is an immune-mediated systemic inflammatory disease triggered by gluten ingestion in genetically predisposed individuals with a wide spectrum of sings and symptoms. Genetic predisposition is strongly associated with HLA-DQ2 and DQ8 heterodimers (HD), also related to a higher risk of occurrence in other autoimmune conditions. Objective: To investigate clinical and immunogenetic characteristics of patients with celiac disease diagnosed in a tertiary center. The data collected retrospectively from medical records from 2008.-2018. included age at the time of diagnosis, clinical presentation, results of specific antibody testing, small bowel biopsy and HLA typing A total of 55 patients were enrolled, 29 females and 26 males (1.12:1), mean age 11.7 ± 4.62 years. A classical form of CD (diarrhea, abdominal distension, failure to thrive) was found in 22 patients, (mean age at diagnosis 3.41±3, 23 yrs, median 1, 88). 18 patients had an atypical, extraintestinal presentation (mean age 9.31±3, 86 yrs, and median 9 yrs). The asymptomatic disease was found in 15 patients, mainly with diabetes type I (T1D), (mean age 9, 27±2, 67yrs, median 9). Out of 39 patients who underwent HLA typing, 36 patients were positive for either single or double dose of DQ2.5 or DQ8 HD. Among three HD negative patients, one was gene DQB1*02 double dose positive (HD DQ2.2 homozygous), one was positive for DQA gene of DQ2.5 HD, while the third one was negative for all DQA or DQB genes from CD predisposing DQ HDs. A total of 17 patients positive at very high CD risk according to the presence of either DQ2.5 in double dose or heterozygous DQ2.5/DQ8 genotype or double DQB1*02 gene dose (DQ2.5/DQ2.2 genotype) were mainly asymptomatic. Furthermore, among 11 patients positive for DQ2.5/DQ2 or DQ2.5/DQ8 genotype (double HD dose), 7 were also T1D patients, while in the remaining 28 DQ2.5 or DQ8 heterozygous and HD negative patients, only 4 were diagnosed with T1D; the observed difference was statistically significant (p=0, 004). In our group of CD patients, clinical presentation related to age was similar to the literature data, with typical gastrointestinal manifestation in the youngest patients. Considering HLA-DQ heterodimer frequency, our patients had a similar distribution to other European and non-European patients with CD. However, since the majority of children with either DQ2.5 homozygous genotype or DQ2.5/DQ8 heterozygous genotype were CD asymptomatic patients primarily diagnosed with T1D, we would like to emphasize the importance of screening for celiac disease in this group of patients.